2000
DOI: 10.1210/mend.14.5.0444
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analysis of the Rev-erbA and RVR Ligand-Binding Domains Reveals a Large Hydrophobic Surface That Mediates Corepressor Binding and a Ligand Cavity Occupied by Side Chains

Abstract: Rev-erbA/RVR are closely related orphan nuclear receptors (NRs) functioning as dominant transcriptional silencers through an association with the nuclear receptor corepressor N-CoR. In contrast with ligand-regulated NRs, Rev-erbA/RVR lack the ligand-binding domain (LBD) C-terminal activation helix, H12. In the case of retinoid acid receptor and thyroid hormone receptor, ligand binding is thought to reposition H12, causing corepressor dissociation and coactivator recruitment, thus leading to transcriptional act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 55 publications
2
30
0
1
Order By: Relevance
“…Recent structure-function analysis and three-dimensional modeling of Rev-Erb␣ indicated that the structure of the putative ligand cavity is occupied by side chains, suggesting that this receptor may not have any endogenous ligands (41). Therefore, the regulation of Rev-Erb␣ expression constitutes a crucial level of control of receptor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent structure-function analysis and three-dimensional modeling of Rev-Erb␣ indicated that the structure of the putative ligand cavity is occupied by side chains, suggesting that this receptor may not have any endogenous ligands (41). Therefore, the regulation of Rev-Erb␣ expression constitutes a crucial level of control of receptor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the significant impact on myokine expression that regulates inflammation, lipolysis, muscle growth, and the accumulation of body fat underscores the potential therapeutic utility of Rev-erb modulation by inverse agonists/antagonists. However, identification of small molecule regulators will be hindered by the lack of a significant pocket in the ligand binding domain in the Rev-erb/ NR1D subgroup of orphan nuclear receptors (51).…”
Section: Figmentioning
confidence: 99%
“…ROR and Rev-erb share 58% and 37% identical amino acids in the C and E domains respectively. Rev-erbs have no known ligand, lack the AF2-activating domain (AF2-AD) region that is necessary for coactivator binding, bind to DNA as monomers or homodimers, and constitutively repress transcription when bound on their responsive element, known as RevRE (recognized by the monomeric form) or RevDR2 (bound by the homodimer) (Harding & Lazar 1995, Adelmant et al 1996, Renaud et al 2000. In contrast to Rev-erbs, ROR orphan receptors act as constitutive transcriptional activators in the absence of exogenously added ligand through monomeric DNA response elements that are extremely similar to the RevRE.…”
Section: Introductionmentioning
confidence: 99%